2011
DOI: 10.1021/ie201059x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of 1,1,1-Trichloroethane Stimulated by Thermally Activated Persulfate

Abstract: In this study, thermally activated persulfate (PS) to stimulate the oxidation of 1,1,1-trichloroethane (TCA) in groundwater remediation was investigated. The effects of various factors including temperature; initial TCA concentration; PS/ TCA molar ratio; solution pH; and common constituents in groundwater such as Cl À , HCO 3 À , SO 4 2À , and NO 3 À anions and humic acid (HA) were evaluated. The experimental results showed that TCA can be completely oxidized in 2 h at 50 °C with a PS/ TCA molar ratio of 100/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(54 citation statements)
references
References 43 publications
(85 reference statements)
9
43
0
Order By: Relevance
“…As the persulfate dosage increases from 0.2 to 4 mM, the degradation rate constant of CBZ enhances from 0.0034 to 0.0744 min À1 . This phenomenon was also observed by other researchers when treating 1,1,1-trichloroethane (TCA) and methyl tert-butyl ether (MTBE) contaminants at various persulfate dosage in TAP system [19,23]. Furthermore, as shown in the insert image of Fig.…”
Section: Effect Of Persulfate Dosagesupporting
confidence: 81%
“…As the persulfate dosage increases from 0.2 to 4 mM, the degradation rate constant of CBZ enhances from 0.0034 to 0.0744 min À1 . This phenomenon was also observed by other researchers when treating 1,1,1-trichloroethane (TCA) and methyl tert-butyl ether (MTBE) contaminants at various persulfate dosage in TAP system [19,23]. Furthermore, as shown in the insert image of Fig.…”
Section: Effect Of Persulfate Dosagesupporting
confidence: 81%
“…•− [18][19][20][21][22][23]. In this study, k obs of SMZ degradation increased noticeably with an increase in PS concentration ( Fig.…”
Section: Effects Of Ps Concentrationsupporting
confidence: 58%
“…In heat activation, PS is usually utilized as a precursor of SO 4 •− , and symmetrical cleavage of the peroxide bond results in the formation of SO 4 •− , which further oxidizes the pollutants [15]. Several recent studies documented the effectiveness of heat-activated PS oxidation of herbicides [18,19], industrial chemicals [20,21], and pharmaceuticals [22,23]. Heat-activation possesses several advantages compared with other activation approaches.…”
Section: Somentioning
confidence: 99%
See 1 more Smart Citation
“…However, Khan and Adewuyi [46] reported that the absorption and oxidation of nitric oxide (NO) significantly improved with the addition of NaCl in sodium persulfate solutions. In addition, in our previous study of 1,1,1-trichloroethane oxidation stimulated by thermally activated persulfate [47], we found anions Cl À and HCO 3 À had negative effects on TCA removal over the range of 1 to 100 mM.…”
Section: Influences Of Solution Matrix On the Degradation Of Tce In Pmentioning
confidence: 64%